Effect of flame retardant fillers on the fire resistance and physicalmechanical properties of polymeric compositions - Chulieieva, Olena (Eastern-European Journal of Enterprise Technologies, 2017)
An effect of copolymer of ethylene with vinyl acetate of the polymeric matrix and flame retardant fillers on the fire resistance of composite materials was studied. We used of ethylenevinyl acetate copolymer in the research. The content of vinyl acetate is 18 % and 28 %; melt flow index is 1.8 g/10 min and 2.5 g/10 min, respectively. The flame retardant fillers are aluminum oxide trihydrates with an average diameter of particles of 1.5 µm and 3 µm; magnesium oxide dihydrates – 3.0 µm and 3.7 µm; hydromagnesites – 1.5 µm. The fire resistance of polymeric compositions was determined using a method of Oxygen Index. It is shown that in order to achieve Oxygen Index larger than 27 %, the degree of filling of the polymeric compositions based on EVA 1 and EVA 2 has to reach 40‒60 % depending on the chemical composition and properties of the fire retardants. At the same time, applying EVA 2 makes it possible to achieve this indicator at smaller values of the filling. We established regularities in the effect of the nature of a polymeric matrix and flame retardant fillers on the physicalmechanical properties of compositions before and after ageing. An increase in the content of fillers in the polymeric composition results in reduced destructive stress and relative elongation at breaking, while the modulus of elasticity at stretching increases. The results obtained could be applied when designing the formulations of polymeric compositions, which do not support combustion, for cable products, and which allow control over operational characteristics.